Differential role of hypothalamic orexin/hypocretin neurons in reward seeking motivated by cocaine vs. palatable food - Martin-Fardon, Rémi (Addict Biol, 2016)
Hypothalamic orexin/hypocretin (Orx/Hcrt) neurons are thought to mediate both food-reinforced behaviors and behavior motivated by drugs of abuse. However, the relative role of the Orx/Hcrt system in behavior motivated by food vs. drugs of abuse remains unclear. This investigation addressed this question by contrasting hypothalamic Orx/Hcrt neuronal activation associated with reinstatement of reward seeking induced by stimuli conditioned to cocaine (COC) vs. highly palatable food reward, sweetened condensed milk (SCM). Orx/Hcrt neuronal activation in the lateral hypothalamus (LH), dorsomedial hypothalamus (DMH), and perifornical area (PFA), determined by dual c-fos/orx immunocytochemistry, was quantified in rat brains following reinstatement of reward seeking induced by a discriminative stimulus (S(+)) conditioned to COC or SCM. The COC S(+) and SCM S(+) initially produced the same magnitude of reward seeking. However, over four subsequent tests, behavior induced by the SCM S(+) decreased to extinction levels, whereas reinstatement induced by the COC S(+) perseverated at undiminished levels. Following both the first and fourth tests, the percentage of Orx/Hcrt cells expressing Fos was significantly increased in all hypothalamic subregions in rats tested with the COC S(+), but not rats tested with the SCM S(+). These findings point toward a role for the Orx/Hcrt system in perseverating, compulsive-like cocaine seeking but not behavior motivated by palatable food. Moreover, analysis of the Orx/Hcrt recruitment patterns suggests that failure of Orx/Hcrt neurons in the LH to respond to inhibitory inputs from Orx/Hcrt neurons in the DMH/PFA may contribute to the perseverating nature of cocaine seeking.